Commodification of Women's Empowerment (Instagram Community X Case Study) - Siti Maharani Nabilah; Inas Ulfa Hapsari; Novia Anggi (Dinasti Publisher, 2025)
This research examines how Community X, a digital network on Instagram, commodifies the issue of women’s empowerment. Adopting a qualitative descriptive approach and drawing on Vincent Mosco’s commodification theory, the study analyzes how empowerment narratives are packaged as paid training, volunteer programs, and promotional activities based on digital content. The narrative of multitasking mothers is also reproduced in Community X’s content to reinforce gender-biased social expectations, while perpetuating an unequal emotional burden on women. The women’s empowerment ostensibly offered by this digital community does not occur within a neutral space. Rather, it is subordinated to economic interests that capitalize on women’s identities as sources of both symbolic and material production. The findings of this study highlight the importance of critically analysing empowerment discourse within the digital ecosystem to avoid participatory biases that obscure the commodification of women and the dynamics of digital labour relations.